Edith Stein in the Memory of the City of Wrocław - Topp, Izolda (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
The article seeks to explore the role of Edith Stein’s memory in creating the contemporary identity of the city of Wrocław. The author distinguishes between two forms of this memory, that is to say remembrance and symbolic places (lieux de mémoire). The places of remembrance of Edith Stein, who was born in Breslau, are connected with her biography and the time she spend in this city. The symbolic places of the memory of Edith Stein represent the values of her life (such as the European Peace Cross, meticulously analysed by the author). Both forms of memory variously transformed the space of the city in significant landscape.